Automated test case generation for FBD programs implementing reactor protection system software. (5th September 2014) - Jee, Eunkyoung; Shin, Donghwan; Cha, Sungdeok; Lee, Jang‐Soo; Bae, Doo‐Hwan; Brucker, Achim D.; Julliand, Jacques
SUMMARY Automated and effective testing for function block diagram (FBD) programs has become an important issue, as FBD is increasingly used in implementing safety‐critical systems. This work describes an automated test case generation technique for FBD programs and its associated tool—FBDTester. Given an FBD program and desired test coverage criteria, FBDTester generates test requirements and invokes the Satisfiability Modulo Theories solver iteratively to derive a set of test cases. An industrial case study using reactor protection system software shows that the automatically generated test suites detected at least 82% of the known faults, whereas manually generated test cases only detected approximately 35%. Mutation analysis revealed that the automatically generated test suites substantially outperformed manually generated ones. Although test sequence generation requires some manual effort in the current FBDTester, it is apparent that the proposed approach significantly improves the efficiency and the reliability of FBD testing. Copyright © 2014 John Wiley & Sons, Ltd.